Effect of Tillage Management Practices on Soil Physical Properties and Yield of Groundnut in Rice-based Cropping System - Ramachandran, S.; Rao, C. Nagender; Dinesh, D.; Srinivasan, R.; Sankar, M.; Ramesh, T.; Padua, Shelton (International Journal of Bio-resource and Stress Management, 2023)
A Field experiment was conducted to investigate the influence different tillage practices in groundnut yield after different planting method of rice on changes in soil physical properties. Experiment was conducted in a split-plot design with three planting methods of rice viz., Direct seeding of rice, transplanting of rice after puddling and in situ green manuring and transplanting of rice after puddling as main plots and three tillage treatments for groundnut ploughing i.e., Ploughing once+harrowing twice; Ploughing twice+harrowing thrice and Ploughing twice+rotavator twice as sub plots. The result showed that lower bulk density and penetration resistance, MWD and higher porosity, hydraulic conductivity and infiltration rate were influenced by tillage and planting method as well as their interaction. Among tillage methods, ploughing twice+rotavator twice registered higher pod yield of 2.17 t ha-1 which was higher than other tillage treatments. Among planting methods, in situ green manuring and transplanting of rice after puddling recorded significantly higher ground nut pod yield of 2.26 t ha-1 which was 9.49 and 19.6% higher than other planting methods treatments respectively. Ploughing twice+rotavator twice with direct seeding of rice was the superior combination than other treatment combinations with respect to pod yield and yield attributes which in turn indicated by congenial soil physical properties. It was inferred that ploughing with mould board plough followed by rotavator in direct seeding of rice planting it was method favorable for improve groundnut productivity in rice-groundnut system.